2005
DOI: 10.1577/m04-122.1
|View full text |Cite
|
Sign up to set email alerts
|

Winter Ice Processes and Pool Habitat Associated with Two Types of Constructed Instream Structures

Abstract: There is little information on the winter features of salmonid habitats associated with constructed instream structures to provide guidance when planning habitat improvement projects. We assessed winter habitat features for trout of the genera Oncorhynchus and Salvelinus in pools associated with two types of instream structures constructed on a low-gradient reach of a mountain stream in western Wyoming with a mean wetted width of 6.4 m. Pool habitat was affected by temporal variability in ice formations from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Not surprisingly, the focus on winter-related issues in lotic fish research during the last decade or so has provided much new information about overwintering fish. Still, further work is needed so that we may be better able to manage boreal rivers and streams (Cunjak 1996;Huusko and Yrjänä, 1997;Alfredsen and Tesaker 2002;Barrineau et al, 2005). The majority of research conducted on the winter ecology of salmonids has been carried out in small rivers and streams, where the temperature remains a few degrees above zero and with no ice.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the focus on winter-related issues in lotic fish research during the last decade or so has provided much new information about overwintering fish. Still, further work is needed so that we may be better able to manage boreal rivers and streams (Cunjak 1996;Huusko and Yrjänä, 1997;Alfredsen and Tesaker 2002;Barrineau et al, 2005). The majority of research conducted on the winter ecology of salmonids has been carried out in small rivers and streams, where the temperature remains a few degrees above zero and with no ice.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of local pools and slow‐flowing areas upstream of anchor ice dams results in closure of the water table by surface ice, shortening the period of dynamic ice formation. In cases where protruding boulders and coarse bed particles increase turbulence, they may nevertheless also favour the formation of anchor ice dams, since they offer a larger area for adhesion of frazil ice (Barrineau et al. , 2005; Stickler et al.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical studies of the same structure indicated a decrease in flow area during ice conditions, causing an increase in sediment transport above what would occur in the absence of ice (Knack et al 2010). Hanging dams reduced pool volume and increased near-bed velocities at log-plunge structures on the South Cottonwood Creek, Wyoming, both of which increase the potential for scour (Barrineau et al 2005). Ice-control structures meant to hold back ice jams in locations upstream of risk areas have been at risk for scour and erosion, including a structure on the Salmon River in Connecticut (Briggs 2003) and on Cazenovia Creek in New York (USACE 2015).…”
Section: In-stream Structuresmentioning
confidence: 99%